Investigation of the fractionalized polyethylene terephthalate (PET) on the properties of stone mastic asphalt (SMA) mixture as aggregate replacement - Ben Zair, Mohamed Meftah; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin; Ansari, Anwaar Hazoor; Elahi, Zafreen (Elsevier, 2024)
Polyethylene terephthalate (PET) is a widely used plastic that accounts for almost 18 % of global polymer production and is non-biodegradable, making it a major cause of environmental pollution. Innovative solutions are needed to address PET waste management and reduce its impact. This study aims to investigate the impact of adding PET, on the engineering characteristics of a Stone Mastic Asphalt (SMA-20) mixture. Laboratory tests were conducted to assess the volumetric and mechanical properties of asphalt mixes containing different proportions of PET as fine and filler (ranging from 0 % to 30 %) by volume of aggregates. The results show that the PET incorporation into the asphalt mixture has significantly improved the performance. The addition of PET (fine and filler) to asphalt mixtures significantly increases their resilient modulus (MR). The mixtures containing 10 % PET as fine and filler are 20 % and 22 % higher in MR than the control mixture. Moreover, the moisture assessment shows that the PET mixture has a higher tensile strength ratio (TSR) value of 85.9 % and 83.90 % for Fine-10 and Filler-20, thus meeting the AASHTO requirement of ≥80 %. The utilization of PET as aggregate replacement significantly improves the permanent deformation characteristics of asphalt mixtures by decreasing permanent strain. The Fine-20 and Filler-20 revealed promising results by reducing the strain to 0.92 % and 0.81 %. Also, the enhancement in the creep stiffness modulus with 216 and 244 MPa. Furthermore, the addition of PET up to a concentration of 20 % had a beneficial effect on the fatigue response of mixtures. For instance, the failure cycles of the Filler-20 and Fine-10 are 23,231 and 17,521 cycles at a load of 2250 N, whereas the control mixture only endures 8581 failure cycles. In conclusion, PET addition significantly improves SMA properties, promoting waste material utilization in the pavement industry.